Peran Guru Dalam Pemanfaatan Media Pembelajaran Pada Mata Pelajaran Matematika SDN 11 Tilamuta - Tahir, Nevita; Umar, Nur Ainun; Pomalango, Marlin; Naniu, Fiskawati; Tino, Nurlela; Anggriyani Uno, Winda (PT MEDIA JURNAL DAN PENDIDIKAN, 2023)
Learning media are suggestions used in an educational context to help and improve the student learning process. Various learning media such as textbooks, audio, video, images, computer software, models, and other equipment specifically designed to guide, provide information, and facilitate effective understanding of learning material. To increase the effectiveness, efficiency and quality of learning so that it meets expectations, in the learning process teachers are encouraged to carry out various innovations such as by creating learning media, especially in subjects that are considered difficult, so that students will be more interested in learning. In this research, researchers used qualitative descriptive methods. This writing is also based on observations made by researchers at SDN 11 Tilamuta. The results of this research include 1) teachers have played a role in utilizing various types of mathematics learning media, adapted to the material that will be taught. 2) teachers are also involved in motivating and facilitating students in learning activities.